Central Diabetes Insipidus in Acute Myeloid Leukemia with Cytogenetic Abnormality of 9q34 Deletion - Majd Farajallah; Fatima Alkaabi; Arif Alam; Raya Almazrouei (Oman Medical Journal)
Acute myeloid leukemia (AML) is rarely associated with central diabetes insipidus (CDI) with unclear underlying pathophysiological mechanisms. The most commonly reported cytogenetic abnormality in cases of AML-associated CDI is monosomy 7, followed by chromosome 3 abnormalities. We report a case of a woman with newly diagnosed AML with 9q34 deletion (ABL1 gene region), who developed symptoms of polyuria and polydipsia with an investigation confirming CDI. This is the first reported case of cytogenetic abnormality of 9q34 deletion (ABL1 gene region) in AML with CDI.